Measurement of primary cosmic and x-radiation in the South American anomaly at an altitude of 90 km, Part l. Measurement of the primary cosmic radiation intensity. - Becerra, N. E.; Ghielmetti, H. S. (Comisión Nacional de Energía Atómica (Argentina), 1970)
Fil: Becerra, N. E. Comisión Nacional de Energía Atómica; Argentina